Efferent Pathways of the Mouse Lateral Habenula. Issue 1 (30th August 2014) - Quina, Lely A.; Tempest, Lynne; Ng, Lydia; Harris, Julie A.; Ferguson, Susan; Jhou, Thomas C.; Turner, Eric E.
ABSTRACT The lateral habenula (LHb) is part of the habenula complex of the dorsal thalamus. Recent studies of the LHb have focused on its projections to the ventral tegmental area (VTA) and rostromedial tegmental nucleus (RMTg), which contain γ‐aminobutyric acid (GABA)ergic neurons that mediate reward prediction error via inhibition of dopaminergic activity. However, older studies in the rat have also identified LHb outputs to the lateral and posterior hypothalamus, median raphe, dorsal raphe, and dorsal tegmentum. Although these studies have shown that the medial and lateral divisions of the LHb have somewhat distinct projections, the topographic specificity of LHb efferents is not completely understood, and the relative extent of these projections to brainstem targets is unknown. Here we have used anterograde tracing with adeno‐associated virus–mediated expression of green fluorescent protein, combined with serial two‐photon tomography, to map the efferents of the LHb on a standard coordinate system for the entire mouse brain, and reconstruct the efferent pathways of the LHb in three dimensions. Using automated quantitation of fiber density, we show that in addition to the RMTg, the median raphe, caudal dorsal raphe, and pontine central gray are major recipients of LHb efferents. By using retrograde tract tracing with cholera toxin subunit B, we show that LHb neurons projecting to the hypothalamus, VTA, median raphe, caudal dorsal raphe, and pontine central gray reside in characteristic, but sometimes overlapping regions of the LHb. Together these results provide the anatomical basis for systematic studies of LHb function in neural circuits and behavior in mice. J. Comp. Neurol. 523:32–60, 2015. © 2014 Wiley Periodicals, Inc.